(3GdOQ GdeUhf aj Ydhe GdcJGH Gdecfhfs - (3CMeO Hf jhSa Hf YHO GdOGje GdMdHj, CHh GdYHGS, TgGH GdOjf GdeYQha HGdSejf,J (B756 (3g` s ((3HOQ GdOjf GdHTJci s)
(3ChdgG (B:s
(3jHJOF HChd GdbQBf s
(3BNQgG (B:s
(3hjfJgi Hbhdg JYGdi (B:" (3ChdFc dge YPGH Cdje heGdge ef fGUQjf (B" s
(3GdfSNI HgG MhGTs
(3hgh EYQGH GdbQBfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B274 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B211s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B33 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B732s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs